2021
DOI: 10.1021/acs.chemmater.1c00967
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Deliquescence and Amino-Efflorescence of Methylammonium Lead Iodide

Abstract: Driven by the exceptional optoelectronic performance and prospective applications of organic−inorganic hybrid perovskites (HPs), an array of methods to synthesize and process HPs has been developed. Although most studies focus on solution processing, a number of reports have examined vapor-phase effects, such as the unusual liquefaction of HP films when exposed to methylamine (MA 0 ) vapor. Here, using in situ spectroscopy and microscopy, we examine the thermodynamics and kinetics of the liquefaction and recry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…We recently showed that the nucleation and growth rates during amino-efflorescence show an exponentially decreasing and increasing dependence on increasing temperature, respectively. 37 As shown by the red dashed line in Figure 1a, this dependence caused the apparent grain size of thin films to vary from microns at room temperature to millimeters at temperatures near 100 °C. Here, we more thoroughly analyze the crystallinity and orientation of MAPbI 3 thin film samples spin-cast on FTO-coated glass substrates after an aminodeliquescence/efflorescence cycle at a controlled p MA0 and temperature inside a hot-walled quartz tube vacuum reactor.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We recently showed that the nucleation and growth rates during amino-efflorescence show an exponentially decreasing and increasing dependence on increasing temperature, respectively. 37 As shown by the red dashed line in Figure 1a, this dependence caused the apparent grain size of thin films to vary from microns at room temperature to millimeters at temperatures near 100 °C. Here, we more thoroughly analyze the crystallinity and orientation of MAPbI 3 thin film samples spin-cast on FTO-coated glass substrates after an aminodeliquescence/efflorescence cycle at a controlled p MA0 and temperature inside a hot-walled quartz tube vacuum reactor.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…A full list of substrates and their preparation is included in Table S1. For reference, our prior study 37 of amino-deliquescence/efflorescence was performed using spin-cast thin films on fluorinedoped tin oxide (FTO) glass substrates, having a MA 0 (MAPbI 3 ) n (l) contact angle of ∼32°.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations